A case of cornual pregnancy at ten gestational age accompanied by heterotopic pregnancy - Yun, Jisun; Seo, Jong-wook; Lee, In Ok; Chung, Jae Eun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Objective of the study was to report a case of cornual pregnancy at 10 weeks gestational age, accompanied by heterotopic pregnancy. A 41-year-old woman was transferred to the emergency department of the national health insurance service Ilsan hospital at amenorrhea 10 weeks 5 days after being diagnosed of cornual pregnancy from a primary hospital. The patient was nulliparous with a history of 1 induced and 2 missed abortions. Other than a previous myomectomy, her medico-surgical history was not significant. She was initially diagnosed with blight ovum at amenorrhea 8 weeks 4 days, and dilatation and curettage were performed at the primary hospital of which she was referred from. At amenorrhea 10 weeks 5 days, another gestational sac was noted at the left cornu of the uterus by ultrasonography. The tentative diagnosis was cornual pregnancy accompanied by heterotopic pregnancy. Serum ß human chorionic gonadotrophin (hCG) at the time of arrival was 84573.8 mIU/ml. Trans-abdominal ultrasonography showed a mass protruding from the left cornu of the uterine cavity, containing a gestational sac (mean sac diameter 39.0 mm, 10 weeks size) and an embryo of cranio-caudal length of 38.2 mm (10 weeks 5 days size). There was no sign of intraperitoneal hemorrhage. Emergency operation was planned under the diagnosis of cornual pregnancy. Entering the abdominal cavity, a 5×5 cm sized conceptual mass surrounded by thin and fragile myometrium was noted on left uterine cornu. Open wedge resection of the left cornual pregnancy with left salpingectomy was performed. The resected mass was 4.0×3.5 cm2 in size. An embryo with 45 mm size was confirmed inside the mass.